Engaging Online Citizen Scientists and the Consensus Method to Monitor the Marine Biofouling Community - Lawson, Katherine N.; Tracy, Brianna M.; Sharova, Maria; Muirhead, Jim R.; Cawood, Alison (Frontiers in Marine Science, 2022)
Citizen science is an important and useful approach to research that broadens public science engagement and expands the scale at which science can be conducted. Monitoring for marine non-native species has been repeatedly identified as a venue for citizen scientists to make substantial contributions. In this study, we evaluated the accuracy of identifications made by volunteers of marine invertebrates on the project Invader ID, hosted on the online citizen science portal Zooniverse. We tested the efficiency and accuracy of invertebrate identifications made through consensus, where more than one volunteer must agree on a final identification before it is added to the database. Using the Matthew’s Correlation Coefficient, we found that four volunteers in consensus balanced efficiency and accuracy when compared to gold standard scientist identifications. Common, large taxa were identified most accurately; Branching Bryozoa identifications made by four volunteers were 85% accurate, Solitary Tunicates 91% accurate, and Colonial Tunicates 64%. In community-based comparisons, the identity of the taxonomist (volunteer or scientist) had a small impact on overall community composition, while site and salinity gradients had a strong impact on composition. We suggest that citizen science monitoring programs focused on highly recognizable taxonomic groups, or on a few species within those groups that can provide crucial information for managers aiming to quickly identify new invasions. Moreover, long-term assessments of composition could be successfully monitored by volunteers from photographs, helping to bolster understanding of ongoing impacts of invasive species or climate change.